Complete Response of Adult-Onset CNS Langerhans Cell Histiocytosis Documented on 18F-FDG PET/CT. (December 2015) - Kruljac, Ivan; Balenović, Antonija; Gaćina, Petar; Imashuku, Shinsaku; Vrkljan, Milan
Abstract : Abstract: We report a case of a 49-year-old woman with biopsy-proven multisystemic Langerhans cell histiocytosis (LCH) with hypothalamic involvement documented on 18 F-FDG PET/CT. Chemotherapy with a combination of vinblastine, prednisolone, methotrexate, and 6-mercaptopurine was carried out. Two months later, a 90% reduction of the hypothalamic tumor mass was noted on magnetic resonance imaging, but with no signs of pathological 18 F-FDG accumulation. The patient died 4 months later, and we found no signs of LCH on autopsy. Our case highlights the need for further studies regarding the role of 18 F-FDG PET/CT in the assessment of treatment response in patients with LCH.